(Techno)Paganism: An Exploration of Animistic Relations with the Digital - Dos Santos, Victoria (Religions, 2023)
The aim of this paper is to examine and illustrate how the animistic ontology present in neopaganism allows embodied and sensuous interactions with virtual worlds. By considering animism as a strategy with which to rethink human cohabitation with the techno-digital otherness, I will show how neopagans who use computer technology for spiritual purposes experience the online context as an environment where lived religious practices can occur. To do so, I will particularly focus on religious practices taking place in digital games and 3D social virtual platforms due to their ability to induce immersive and interactive experiences. Because neopaganism recognizes the material living world as a central aspect of spiritual experiences, I will explore the ways that the spatial and material dimensions are articulated in neopagan’s online performances, the actions they make possible, and how they enable a more intimate relationship with virtual platforms. I will accompany the theoretical reflection with case studies and interviews with technopagan practitioners experiencing their religion with and within computer technology. This paper also aims to show how this new conception of animism connects to what Mikhail Bakhtin calls “dialogism”, a condition that recognizes the multiplicity of perspectives and voices and denies the possibility of not getting involved with the otherness. For such reasons, approaching the digital through an animistic ontology can help us acknowledge the convergence of humans with the techno-digital otherness and explore, on deeper levels, sensuous and embodied experiences taking place in the religious context.